HUBUNGAN ANTARA PROGRAM KAMPUS BERDAMPAK TERHADAP KEMANDIRIAN BELAJAR MAHASISWA PENDIDIKAN SOSIOLOGI UNIVERSITAS MATARAM - Auliya Ataki, Ruli; Sukardi; Malik, Imam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the relationship between the Kampus Berdampak program and students' learning independence in the Sociology Education Study Program at the University of Mataram. The research uses a quantitative correlational approach. A sample of 136 students was determined using the Slovin formula with a random sampling technique. Data collection was conducted through an online questionnaire using a four-point Likert scale, which had passed validity and reliability tests. The results of the hypothesis test using Pearson's product-moment correlation showed a significant positive relationship between the Kampus Berdampak program and learning independence. This is evidenced by a correlation value of 0.637 with a coefficient of determination of 40.5%. These findings imply that the integration of socially impactful programs can effectively develop students' learning independence in higher education environments.